Boredom in the Workplace: Reasons, Impact, and Solutions. (1st February 2016) - Cleary, Michelle; Sayers, Jan; Lopez, Violeta; Hungerford, Catherine
Abstract : Boredom in the workplace is not uncommon, and has been discussed widely in the academic literature in relation to the associated costs to individuals and organizations. Boredom can give rise to errors, adverse patient events, and decreased productivity—costly and unnecessary outcomes for consumers, employees, and organizations alike. As a function of boredom, individuals may feel over-worked or under-employed, and become distracted, stressed, or disillusioned. Staff who are bored also are less likely to engage with or focus on their work. In this article, we consider the nature of boredom and also the reasons why employees, including mental health nurses, become bored in the workplace. We also discuss the role that can be taken by employees and employers to recognise and address the problem of boredom and we consider how best to develop sustainable workplaces that are characterised by engaged employees who provide the best possible service in healthcare settings.